Analysis of clinical and histopathology characteristics of asymptomatic and pauci ⁃ symptomatic hyperCKemia - YUAN Yu‑jing; LIU Chang; XIE Zhi‑ying; ZHAO Ya‑wen; MENG Ling‑chao; LÜ He; WANG Zhao‑xia; YUAN Yun; ZHANG Wei (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Objective To evaluate the diagnostic value of skeletal muscle biopsy in asymptomatic and pauci‑symptomatic hyperCKemia. Methods and Results A total of 146 patients with asymptomatic or pauci ‑ symptomatic hyperCKemia diagnosed in Peking University First Hospital from July 2020 to February 2023 were selected, and skeletal muscle biopsy was performed. About 72.60% (106/146) had histological changes, including muscular dystrophy (n = 73), inflammatory or necrotizing myopathy (n = 16), other myopathy (n = 15), and neurogenic skeletal muscle damage (n = 2). The positive rate of pathological diagnosis was 50.68% (74/146), including muscular dystrophy 82.43% (61/74), inflammatory myopathy 8.11% (6/74) and metabolic myopathy 9.46% (7/74). The positive rate of etiological diagnosis was 85.62% (125/146), including muscular dystrophy 67.20% (84/125), inflammatory myopathy 13.60% (17/125), metabolic myopathy 7.20% (9/125) and other causes 12% (15/125). Compared with different subgroups, the proportion of pathological changes (χ2 = 14.043, P = 0.000; χ2 = 12.740, P = 0.000), the positive rate of pathological diagnosis (χ2 = 10.641, P = 0.001; χ2 = 25.530, P = 0.000) and etiological diagnosis (Fisher's exact probability: P = 0.001; χ2 = 10.811, P = 0.001) in the significantly elevated creatine kinase (CK) level group and the adolescent group was significantly higher than those in the mildly elevated CK level group and the adult group. The positive rate of pathological diagnosis in the asymptomatic group was higher than the pauci‑symptomatic group (χ2 = 4.792, P = 0.029). There were significant differences in the etiological ratio between the mildly elevated CK level group and the significantly elevated CK level group (Fisher's exact probability: P = 0.000), the adolescent group and the adult group (χ2 = 86.149, P = 0.000), and the asymptomatic group and the pauci ‑ symptomatic group (χ2 = 20.608, P = 0.000). Conclusions Skeletal muscle biopsy was important in etiological diagnosis of asymptomatic and pauci‑symptomatic hyperCKemia. Muscular dystrophy is a common cause of asymptomatic and pauci‑symptomatic hyperCKemia.